Proceedings of the 25th Conference on Winter Simulation - WSC '93 1993
DOI: 10.1145/256563.256610
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the modeling, scheduling and control of flexible automation

Abstract: This paper initially discusses the state-of-the-art and the current limitations in the modeling, scheduling and control of flexible automation. To model flexible automation, it is argued that the simulation tools must provide enhanced capabilities to consider both controller interactions and the flow of resources that support production.It is also demonstrated that scheduling and control must be considered concurrently in real-time to effectively manage flexible manufacturing systems (FMSs). The complexity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Denote by w OPT (I ) the length of an optimal schedule of an instance I . First, we show that an optimal schedule can be obtained by relaxing the parallelism constraint 5 of each job by one. Specifically, if for all j, we run J j in parallel on ρ j + 1 (instead of ρ j ) machines, we can obtain a schedule of length w OPT (I ).…”
Section: Uniform Machinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Denote by w OPT (I ) the length of an optimal schedule of an instance I . First, we show that an optimal schedule can be obtained by relaxing the parallelism constraint 5 of each job by one. Specifically, if for all j, we run J j in parallel on ρ j + 1 (instead of ρ j ) machines, we can obtain a schedule of length w OPT (I ).…”
Section: Uniform Machinesmentioning
confidence: 99%
“…Production processes [5] typically involve the usage of consumable resources (i.e., special materials) which cannot migrate from one machine to another, and mobile resources (e.g., human supervision), which allow flexibility in the choice of machines. The maximal amount of consumable resources determines the allotment parameter of a production process; the available amount of mobile resources determines its parallelism parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier simulation studies conducted in our laboratory demonstrated the importance of modeling controller interactions which coordinate the flow of all entities including jobs and supporting resources, such as tools (see Dullum andDavis 1992 andDavis et al 1993). As a result of this study, we now develop the complete object-oriented definition of the modeled system before attempting to employ a simulation language.…”
Section: The Modeling Approachmentioning
confidence: 99%
“…To this end, we have developed an even more comprehensive modeling paradigm called the Hierarchical Object-Oriented Programmable Logic Simulator (HOOPLS), which simulates the distributed control architecture by modeling the interactions among the controllers, see Davis, Macro, and Setterdahl (1997) and Davis, Setterdahl, Macro, Izokaitis, and Bauman (1993). The HOOPLS paradigm is based upon the belief that interactions among the controllers must be considered by the simulation model in order to accurately model a system with a distributed control architecture.…”
Section: Distributed Systemsmentioning
confidence: 99%